Popping of Graphite Oxide: Application in Preparing Metal Nanoparticle Catalysts. (14th July 2015) - Gao, Yongjun; Chen, Xi; Zhang, Jiaguang; Asakura, Hiroyuki; Tanaka, Tsunehiro; Teramura, Kentaro; Ma, Ding; Yan, Ning
<x xml:space="preserve">Abstract</x> A popcorn‐like transformation of graphite oxide (GO) is reported and used to synthesize metal nanoparticle catalysts. The popping step is unique and essential, not only generating a high‐surface‐area support but also partially decomposing the metal precursors to form well‐separated metal oxide nuclei, which would further evolve into highly dispersed and uniform‐sized nanoparticles in the subsequent reduction.